John Theophilus Desaguliers: A Newtonian between patronage and market relations - Soares, Luiz Carlos (Circumscribere International Journal for the History of Science, 2016)
The dissemination of the mechanical and Newtonian experimental philosophy in 18th-century England arose fascination in relation to the possible application of this new knowledge to the needs of productive life and the general welfare of the population. The activity of many independent and/or itinerant lecturers proved to be fundamental to spread the Newtonian philosophy and allow for the emergence of an ideal of applied science. In the present paper I discuss the intellectual trajectory of John Theophilus Desaguliers (1683-1744), who was the curator, or ‘official experimenter’, of the Royal Society of London and became a pioneer in the spreading of Newtonianism, as well as one of the most important and most respected independent lecturers on mechanical and experimental philosophy in the first half of the 18th century.